Degree of bullying against Academic gifted students from their point of view and their need for psychological counseling - AlKandari, Athari Jafar; AlZayed, Safeya Taha (Journal of Educational and Psychological Sciences, 2019)
The aim of the research was to identify the degree of bullying against the academic gifted and their need for psychological guidance, The research community was all the students in Sabah Al-Ahmad Center for Creativity and Talent in the State of Kuwait classes, The sample consisted of (210) students (113) male and (97) female from grade six to ten, was selected as purposive sample, The data were collected by semi-open interviews, The results indicated that 61% of the students admitted to being subjected to violence and abuse during their life stages, 85% of them were bullying verbally conversely 15% were bulling physically, and 86% were directly bullied while 14% indirectly bullied. That found show the high degree of exposure of talented people to proliferate during their life stages is high. They have been victims of violence and verbal and physical abuse, and there is an urgent need to develop preventive and curative guidance programs